Effect of simvastatin on osteogenesis of the extremity bones in aging rats. (2nd January 2023) - Wang, Mengran; Li, Haowei; Tang, Jiaxin; Xi, Yue; Chen, Shiyi; Liu, Ming
ABSTRACT: Purpose: Simvastatin is a prodrug of the potent 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor. The main purpose of the current study is to assess the accurate function of simvastatin on osteoporosis of extremity bones in aging rats. Materials and methods: Fifty 15-month-old SD rats were divided into five groups (four simvastatin groups and one control group). The rats in four simvastatin groups were fed with different doses of simvastatin (5, 10, 20, and 40 mg/kg/d, respectively) for 3 months, whereas the rats in control group were fed the equal physiological saline. Calcium (Ca), phosphorus (P), and the lipid spectrum in serum were measured. Biochemical markers of bone metabolism, osteocalcin (OC), and tartrate-resistant acid phosphatase (Trap-5b), were analyzed using ELISA. The content of adipocytes in bone marrow was analyzed by histological staining. Finally, the bone quality of the femur and tibia were evaluated using dual-energy X-ray absorptiometry (DEXA), peri-quantity CT (pQCT), and the 3-point bending biomechanical test. Results: Simvastatin reduced serum triglycerides (TG), and 10 mg/kg/d of simvastatin significantly reduced the content of adipocytes in bone marrow compared to the control group. However, statistically significant differences between the simvastatin groups and the control group were not found in the CA, P, OC, Trap-5b, or the evaluation indexes of bone quality from DEXA, pQCT, and biomechanical tests. Conclusion: Simvastatin could not prevent osteoporosis of the extremity bones in aging rats.